1974
DOI: 10.1172/jci107766
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of In Vivo Insulin Secretion by Prostaglandin E1

Abstract: A B S T R A C T To determine the effect of prostaglandin E1 (PGE1) infusion upon in vivo insulin secretion, serum insulin responses after an intravenous glucose pulse (2 g) were measured before and during an intravenous infusion of PGE1 (10 Ag/min) in 11 anesthetized dogs. Circulating insulin decreased significantly during PGE1 infusion, and insulin responses after glucose during PGE1 infusion were significantly less than control responses. Three dogs received PGE1 infusions into the thoracic aorta to preclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 15 publications
3
43
0
Order By: Relevance
“…The only endogenous substances which have been demonstrated to be inhibitory in normal humans are catecholamines and somatostatin (7)(8)(9)(10). We have previously reported that prostaglandins of the E series inhibit glucose-induced secretion in vivo in dogs (11,12). Unlike catecholamines and somatostatin, however, inhibition by prostaglandin E of insulin secretion is not reversed by a-adrenergic blockade (11,13 25,30,45,60,90, and 120 min after the intravenous pulses had been given.…”
Section: Introductionmentioning
confidence: 99%
“…The only endogenous substances which have been demonstrated to be inhibitory in normal humans are catecholamines and somatostatin (7)(8)(9)(10). We have previously reported that prostaglandins of the E series inhibit glucose-induced secretion in vivo in dogs (11,12). Unlike catecholamines and somatostatin, however, inhibition by prostaglandin E of insulin secretion is not reversed by a-adrenergic blockade (11,13 25,30,45,60,90, and 120 min after the intravenous pulses had been given.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, glucose, in addition to dominant positive signals for insulin release, also provides endogenous negative modulators (e.g., PGE 2 ). Indeed, in ␤ cells, inhibition of PGE 2 synthesis potentiates glucose-induced insulin release (50,51,70,71).…”
mentioning
confidence: 99%
“…Prostaglandin E (PGE)l is synthesized by pancreatic islets of Langerhans (1) and inhibits insulin secretion in vivo (2,3). This effect appears to be independent of the alpha adrenergic nervous system because it persists during blockade of alpha adrenergic receptors (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…This effect appears to be independent of the alpha adrenergic nervous system because it persists during blockade of alpha adrenergic receptors (2)(3)(4). Serotonin has also been identified within the islet (5,6) and has also been shown to inhibit insulin secretion (7)(8)(9), but it is unclear whether or not this effect of serotonin is related to alpha adrenergic activ-ity.…”
Section: Introductionmentioning
confidence: 99%